The Importance of Ecosystem/Watershed Management Knowledge in Environmental Engineering Education - Vedat Yılmaz (Doğal Afetler ve Çevre Dergisi)
Although environmental engineering -primarily focusing on healthy water supply and disposal of wastewater- incorporates study areas of various engineering disciplines, it has also undertaken a wide range of activities such as infrastructure activities, climate change, waste management, health and safety, environmental management and etc. since 70’s. The areas of engineering expertise, in line with changing technological approaches and social needs, are undergoing change and transformation over the years. Environmental problems are beyond local boundaries and it is necessary to understand the holistic (integrated) interactions of the effects of engineering applications over ecosystems on a global scale. For example, big dams have been built as well as projecting dozens of river-type hydropower projects in the same river basin. The environmental risks of each individual project should be modeled but also the overall domino effects should take into consideration. It is inevitable to evaluate the effects that the activities will have on the ecosystem with some tools such as Environmental Impact Assessment (EIA), Environmental Risk Assessment (ERA) and Life Cycle Analysis (LCA) for this purpose. Today, out of 52 universities in Turkey, 46 of them gives undergraduate level education in their environmental engineering departments and both the departmental curriculum and the specialization of the faculty members are very different in these departments. Therefore, the knowledge and experience of environmental management can not be at the same level. This should be taken into consideration in the accreditation process by the Association of Engineering Education Programs Evaluation and Accreditation (MÜDEK). In this study the priority of watershed management to solve the environmental problems was verified, and the level of ecosystem/watershed management awareness was evaluated in the undergraduate course curriculums of environmental engineering departments in our country.